Monitoring microclimatic conditions in classrooms of various school types. a Slovak case study - Turekova, Ivana; Cabaj, Michal; Markova, Iveta (Frontiers in Built Environment, 2026)
Schools operate in existing buildings owned by cities and municipalities, encompassing various building types. This paper presents results of microclimatic measurements in selected classrooms located in two distinct building types: a 19th century manor house and a school building from the 1960s. The measured parameters were temperature, relative humidity (RH), and CO2 concentration. The position of the measuring device within the room did not appreciably influence the recorded values. Simultaneously, a strong effect of natural ventilation on CO2 concentration was demonstrated. Building type did not materially affect the observed parameters. Notably, CO2 concentrations during lessons exceeded the recommended limit of 1,000 ppm and did not decrease to ambient outdoor levels.